Crime and criminality a multidisciplinary approach - Taylor, Sandie (Routledge, Taylor & Francis Group, 2016)
The question of 'why' and 'how' certain individuals are drawn towards behaving in a way that contravenes the 'Law of the Land' is not an easy one to address. Researchers from various different fields have nevertheless attempted to develop theoretical explanations for the existence of different types of crime and why some individuals commit such acts. Crime and Criminality draws on criminology, sociology, psychology and neuroscience to offer a balanced perspective of crime, the criminal and criminality.